Reviewers - Redakcja, (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2022)
Barbara Bombi, School of History, University of Kent Megan Cassidy-Welch, Institute for Religion and Critical Inquiry, Australian Catholic University Peter Edbury, Emeritus, School of History, Archaeology and Religion, Cardiff University Rafał Eysymontt, Instytut Historii Sztuki, Uniwersytet Wrocławski Marie-Luise Favreau-Lilie, Emeritus, Fachbereich Geschichts und Kulturwissenschaften, Freie Universität Berlin Christian Gahlbeck, Geheimes Staatsarchiv Preußischer Kulturbesitz, Berlin Mateusz Goliński, Instytut Historyczny, Uniwersytet Wrocławski Dieter Heckmann, Emeritus, Geheimes Staatsarchiv Preußischer Kulturbesitz, Berlin Marie-Luise Heckmann, Historisches Institut, Universität Potsdam Shlomo Lotan, Department of Land of Israel Studies and Archaeology, Bar-Ilan University, Ramat-Gan Rory MacLellan, Historic Royal Palaces, The Tower of London Beata Możejko, Instytut Historii, Uniwersytet Gdański Piotr Oliński, Instytut Historii i Archiwistyki, Uniwersytet Mikołaja Kopernika w Toruniu Luís Filipe de Oliveira, Faculdade de Ciências Humanas e Sociais, Universidade do Algarve Marek Smoliński, Instytut Historii, Uniwersytet Gdański Jesús Ángel Solórzano-Telechea, Departamento de Ciencias Históricas, Universidad de Cantabria Beth Spacey, School of Historical and Philosophical Inquiry, Faculty of Humanities and Social Sciences, the University of Queensland Tomasz Torbus, Instytut Historii Sztuki, Uniwersytet Gdański Christian Vogel, Historisches Institut, Universität des Saarlandes Thomas Zotz, Emeritus, Philisophische Fakultät, Universität Freiburg